Forecasting Import Demand of Table Grapes: Empirical Evidence from Thailand - Jatuporn , Chalermpon; Sukprasert, Patana; Tongchure, Siros; Suvanvihok, Vasu; Thongkaew, Supat (Asian Journal of Agriculture and Rural Development, 2020)
The purpose of this study is to forecast the import demand of table grapes of Thailand using monthly time series from January 2007 to April 2020. The ADF unit root test is used for stationarity checking, and seasonal autoregressive integrated moving average (SARIMA) is applied to forecast the import demand of table grapes. The results revealed that the integration of time series was in the first difference for non-seasonal and seasonal order. The best-fitted forecasting model was SARIMA(1,1,3)(2,1,0)12. The forecasted period for the next eight months showed the import demand of table grapes of Thailand that is slightly decreased by an average of 11.398 percent, with overall expected to decrease by an average of 15.218 percent in 2020.